Odpowiedzi

2010-02-17T20:39:05+01:00
A)
-3a-[6a-4b-(5a-5b)]

-3a-6a+5a +4b-5b= -4a-b


b) -6x-4y-[-(6x-2y-3x+y)-4x+12+10y]

x-15y-12
1 5 1
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-17T20:43:01+01:00
-3a-[6a-4b-(5a-5b)] = -3a-(6a-4b -5a +5b)= -3a -6a +4b +5a -5b=
= -4a -b

-6x-4y-[-(6x-2y-3x+y)-4x+12+10y] =
= -6x-4y-( -6x + 2y + 3x -y -4x + 12 + 10y) =
= -6x-4y + 6x -2y -3x +y +4x -12 -10y =
= x -15y -12
1 5 1
2010-02-17T20:43:14+01:00
A) -3a-[6a-4b-(5a-5b)]= -3a-(6a-4b-5a-5b)= -3a-6a+4b+5a+5b= -4a-b

b) -6x-4y-[-(6x-2y-3x+y)-4x+12+10y]= -6x-4y-(-6x+2y+3x-y-4x+12+10y)= -6x-4y+6x-2y-3x+y+4x-12-10y= -15y+x-12
1 5 1